(3GdoYeOI aj UfGYI GdTYQ hfbOgs - (3GdMSf Hf QTjb GdbjQhGfj, CHh Ydj , GHf QTjb,J (B463 (3g` s
(3ChdgG (B:s
(3abO hLOJ GdTYQ CcHQ Ydhe GdYQH, hChaQ MXhX GdBOGH s
(3BNQgG (B:s
(3hbhdg CXddJ HeYfi UHQJ, hjQhi HGdUGO, hGddg CYde HGdUhGH s
(3GdfSNI HgG MhGTs
(3GdfUa GdChd ef GdcJGHs
(3HgG fXGe GdJYbjHIs
(3fSNI KGdKIs
(3HChdgG agQS ddehVhYGJ hJQLeI ddeDda efbhdI ef hajGJ GdCYjGf dGHf NdcGf s
(3bQf GdfSN (B:s
Keywords: (3GdCOHs